STATUS DAN PERAN BADAN PERMUSYAWARATAN DESA (BPD) DI DESA BARAN MELINTANG KECAMATAN PULAU MERBAU KABUPATEN KEPULAUAN MERANTI - Said Ridho Amal; Syamsul Bahri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research was conducted in the village of Baran Melintang KecamatanPulau Merbau Kabupaten Kepulauan Meranti in order to obtain information aboutthe role of the Implementation of the Village Consultative Body. Problems in thisstudy were (1) A BPD role as a partner in the Village Head support the success ofdevelopment in 2014 ago in the village of Baran Melintang Kecamatan PulauMerbau Kabupaten Kepulauan Meranti? (2) What factors influence theimplementation of the BPD's role in carrying out its function as a partner in theVillage barrage of Village Baran Melintang Kecamatan Pulau Merbau KabupatenKepulauan Meranti. The title of this research is "Status and Role of the VillageConsultative Body (BPD) in the village of Baran Melintang Kecamatan PulauMerbau Kabupaten Kepulauan Meranti". This research is a quantitativedescriptive described hereinafter in accordance with the actual situation. Thecollection of data through observation and direct interview to the respondent.Because the number of people in the village of Baran Melintang Across all thenumerous techniques used sampling using purposive sampling technique is atechnique determination of sample with a certain consideration. The number ofsamples in this study as many as 47 people. The data collected from the researchresults, processed using frequency tables with percentages. The results showedthat the role of the Village Consultative Body in the village of Baran Melintangdid not act well, this is evidenced by its lower respondents' assessment of eachimplementation role Transverse BPD Baran Melintang and his lack of attentionfrom the local government of the factors that hinder the implementation of therole of BPD.Keywords: Status Role (BPD)